Local government website accessibility: Evidence from Poland - Karol Król; Dariusz Zdonek (Administrative Sciences, 2020)
The paper investigates the accessibility of local government websites. It focuses in particular on disability, e-administration, and web accessibility standards for the visually impaired. The research involved 182 websites of local government bodies of the Ma±opolskie Voivodeship (Poland). It employed selected automated testing applications. The occurrence of selected accessibility tools on the websites was verified with a cognitive walkthrough. A questionnaire survey was conducted as well. Results of the automatic measurements were standardized using the unitarization method. The effort yielded an aggregate final score for each website in the form of the AAR (Aggregate Accessibility Rating). It was used to build a ranking list of the websites and order them by the accessibility criterion. The websites achieved 57.23% of the available AAR points in total. This indicates there is a great opportunity for improvement in the accessibility of the investigated websites (in the employed research design). Moreover, municipalities were found to be heavily committed to the questionnaire survey, which is indicative of the importance and relevance of the problem of accessibility and quality of public websites.
Keywords: 350; electronic administration; accessibility guidelines; accessibility audits; e-administration; e-services